Implementation of a novel ultrasound training programme for midwives in Malawi: A mixed methods evaluation using the RE-AIM framework - Viner, Alexandra C.; Malata, Monica P.; Mtende, Medrina; Membe-Gadama, Gladys; Masamba, Martha; Makwakwa, Enita; Bamuya, Catherine; Lissauer, David; Stock, Sarah J.; Norman, Jane E.; Reynolds, Rebecca M.; Magowan, Brian; et al. (Frontiers in Health Services, 2023)
Introduction Despite recommendation that all women receive an ultrasound in pregnancy prior to 24 weeks’, this remains unavailable to many women in low-income countries where trained practitioners are scarce. Although many programmes have demonstrated efficacy, few have achieved longterm sustainability, with a lack of information about how best to implement such programmes. This mixed-methods study aimed to evaluate the implementation of a novel education package to teach ultrasound-naive midwives in Malawi basic obstetric ultrasound, assessing its impact in the context of the Reach, Effectiveness, Adoption, Implementation and Maintenance (RE-AIM) framework. Methods The study ran across six sites in Malawi between October 2020 and June 2021, encompassing three phases; pre-implementation, implementation and post-implementation. 29 midwives underwent a bespoke education package with matched pre and post course surveys assessed their knowledge, attitudes and confidence and ‘hands on’ assessments evaluating practical skills. Training evaluation forms and in-depth interviews explored their satisfaction with the package, with repeat assessment and remote image review evaluating maintenance of skills. Results 28/29 midwives completed the training, with significant increases in knowledge, confidence and practical skills. Adherence to the education package varied, however many changes to the proposed methodology were adaptive and appeared to facilitate the efficacy of the programme. Unfortunately, despite reporting approval regarding the training itself, satisfaction regarding supervision and follow up was mixed, reflecting the difficulties encountered with providing ongoing in-person and remote support. Conclusion This programme was successful in improving trainees’ knowledge, confidence and skill in performing basic obstetric ultrasound, largely on account of an adaptive approach to implementation. The maintenance of ongoing support was challenging, reflected by trainee dissatisfaction. By evaluating the success of this education package based on its implementation and not just its efficacy, we have generated new insights into the barriers to sustainable upscale, specifically those surrounding maintenance.